A meta-synthesis on parenting a child with autism - Ooi K; Ong YS; Jacob SA; Khan TM (Neuropsychiatric Disease and Treatment, 2016)
Khim Lynn Ooi, Yin Sin Ong, Sabrina Anne Jacob, Tahir Mehmood Khan School of Pharmacy, Monash University Malaysia, Bandar Sunway, Selangor, Malaysia Background: The lifelong nature of autism in a child has deep implications on parents as they are faced with a range of challenges and emotional consequences in raising the child. The aim of this meta-synthesis was to explore the perspectives of parents in raising a child with autism in the childhood period to gain an insight of the adaptations and beliefs of parents toward autism, their family and social experiences, as well as their perceptions toward health and educational services.Methods: A systematic search of six databases (PubMed, EMBASE, PsychInfo, Cochrane Central Register of Controlled Trials, Cochrane Database of Systematic Reviews, and Database of Abstracts of Reviews of Effects [DARE]) was conducted from inception up to September 30, 2014. Full-text English articles of qualitative studies describing parents’ perceptions relating to the care of children younger than 12 years of age and diagnosed with a sole disorder of autism were included.Results: A total of 50 eligible articles were appraised and analyzed, identifying four core themes encompassing all thoughts, emotions, and experiences commonly expressed by parents: 1) The Parent, 2) Impact on the Family, 3) Social Impact, and 4) Health and Educational Services. Findings revealed that parents who have a child with autism experienced multiple challenges in different aspects of care, impacting on parents’ stress and adaptation.Conclusion: Health care provision should be family centered, addressing and supporting the needs of the whole family and not just the affected child, to ensure the family’s well-being and quality of life in the face of a diagnosis of autism. Keywords: autistic spectrum disorder, childhood, adaptation, meta-synthesis